New Vision of Theatre - Reception and Influence of International Avant-garde Theatre in Croatia - Magaš Bilandžić, Lovorka (Array, 2014)
Theatre had a prominent place within the context of radical Avant-gardes and became a platform for redefining traditional concepts and examining new theoretical postulates. Throughout Europe, in the second and third decade of the 20th century, many authors who were simultaneously active in that period contributed to the realization of the new vision of theatre. Their explorations ranged from the deliberations on the mechanical, plastic and marionette theatre to the experimentation with an abstract theatrical act, minimized to a game of shapes, colours and lights on stage. The new understanding of scenography and the explorations of the movement of the body in space – characteristic of Constructivist, Cubist and Futurist implementations and practices of artists at the Bauhaus – were comprehensively presented to the public at theatre exhibitions, organized by Friedrich Kiesler, in Vienna (1924) and New York (1926). Croatian artists, namely Ljubo Babić and Sergije Glumac participated in Kiesler’s International Theatre Exposition in New York, and presented their visions of theatre alongside the leading protagonists of the Avant-garde of that time. Croatian public was introduced to the new deliberations on theatre on multiple levels, whereby the artists who had resided in European capitals (i.e. Paris, Berlin, etc.) played a significant role, same as the international journals and articles about the new developments in European theatre which were published within the pages of local theatre and Avant-garde journals such as Comoedie and Zenit. The beginning of the 1920s was also marked by important advances achieved in the Zagreb art scene, prominent among them being the Avant-garde theatrical experiments of high school students led by Josip Seissel, and Ljubo Babić’s and Branko Gavella’s "scenography of meaning", which were realized on the stage of the National Theatre. This presentation will address the transfer of influences and the implementation of various aspects of the international Avantgarde theatre in the Central European context. Furthermore, special attention will be placed upon the practices of Sergije Glumac and other Croatian artists who, by exploring the concept of "new theatre", surpassed the local framework and became part of the Avant-garde tendencies which marked the 1920s and redefined the notion of theatrical space and performing arts.